Effects of trade openness on environmental quality: Evidence from developing countries - Diem Thi Thuy Pham; Hoai Trong Nguyen (Journal of Applied Economics, 2024)
This paper uses the Bayesian model averaging approach to investigate the effects of trade openness on environmental quality in 64 selected developing countries for the period of 2003-2017. We find no evidence of a statistically significant effect of trade openness on environmental pollution in our sampled developing countries; however, our results show weak support for the pollution haven hypothesis. Besides trade openness, our findings indicate that financial openness, renewable energy consumption, and capital abundance are essential drivers of environmental quality, which appear to reduce carbon dioxide (CO2) emissions. In contrast, inward foreign direct investment and income harm environmental quality in the context of the developing countries studied. Based on our overall results, this paper suggests some strong policy recommendations for improving the environmental quality to achieve sustainable development under the background of a low-carbon economy in these nations.
Keywords: 330; Carbon dioxide (CO2) emissions; developing countries; environmental quality; Trade openness